Implementasi Filantropi Pendidikan di Yayasan Baitul Maal BRILiaN Yogyakarta - Fawaiz, Aiz Affwa; Aditya Prayoga, M. Rizky; F, Hasriyah; Anisa Widiawati (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2024)
Education is an important aspect in efforts to progress a nation, so in this case philanthropy has a role in pursuing education which often becomes a polemic in Indonesia to this day. The research results show that the Baitul Mal BRILiant Foundation is an institution that collects, manages and distributes zakat, infaq and alms funds from BRI employees throughout Indonesia which are divided into various regions, one of which is in the city of Yogyakarta. YBM BRILiant also focuses on implementing educational philanthropy activities, namely firstly My Scholarship which is a scholarship program intended for students from elementary school to tertiary level from mustahik families, secondly Smart Scholarship is a one year scholarship program and is intended for students High School (SMA) which is preparing for college level and the Bright Scholarship which is a three year scholarship program intended for students at state universities. So the orientation of the BRILian Foundation here is a form of their commitment to building vertical mobility and quality of life for poor families, as well as realizing the dreams of the nation's generations. This research uses a qualitative method with a descriptive approach. The research was conducted to gain a deeper understanding of the experiences, perceptions and views related to the YBM BRILianN program in implementing Educational Philanthropy. Â  Keywords: Educational Philanthropy, YBM BRILLIANT, Entrepreneurship